Analysis of wear properties of granite dust filled polymer composite for wind turbine blade - Joy Mathavan, J.; Patnaik, A. (Elsevier., 2020)
Efficient usage of wind energy by establishing a suitable material for wind turbine blade is considered in this paper. Aluminium alloys and coated timber were used as blade material in the early stage and are discarded for various reasons including their life time and their efficiency. New polymer based materials such as Carbon fiber, Glass fiber, and Aramid fiber with different kinds of resins are being used as wind turbine blade material these days. As a new trend, granite dust is filled with the polymer material to improve its qualities like hardness and durability. It is tested for wear properties in Air jet erosion tester by varying the angle of impingement keeping other factors constant. Its mechanical properties like tensile stress, hardness and density values are calculated and plotted in graphs. The obtained results demonstrate how the wear properties of these samples changed with the impingement angle.
Keywords: Aramid fiber.; Granite dust.; Tensile strength.